Factors affecting physician professional satisfaction and their implications for patient care, health systems, and health policy - Friedberg, Mark W. (Research report (Rand Corporation), 2013)
One of the American Medical Association's core strategic objectives is to advance health care delivery and payment models that enable high-quality, affordable care and restore and preserve physician satisfaction. Such changes could yield a more sustainable and effective health care system with highly motivated physicians. To that end, the AMA asked RAND Health to characterize the factors that lead to physician satisfaction. RAND sought to identify high-priority determinants of professional satisfaction that can be targeted within a variety of practice types, especially as smaller and independent practices are purchased by or become affiliated with hospitals and larger delivery systems. Researchers gathered data from 30 physician practices in six states, using a combination of surveys and semistructured interviews. This report presents the results of the subsequent analysis, addressing such areas as physicians' perceptions of the quality of care, use of electronic health records, autonomy, practice leadership, and work quantity and pace. Among other things, the researchers found that physicians who perceived themselves or their practices as providing high-quality care reported better professional satisfaction. Physicians, especially those in primary care, were frustrated when demands for greater quantity of care limited the time they could spend with each patient, detracting from the quality of care in some cases. Electronic health records were a source of both promise and frustration, with major concerns about interoperability between systems and with the amount of physician time involved in data entry--